The language of men : a memoir - D'Aries, Anthony. 1982- (Albany : Hudson Whitman/Excelsior College Press, 2012)
An incisive, eloquent literary memoir that transports us to the crossroads of gender and history, then leads us through the unsettling terrain that shapes fathers, sons, brothers, and husbands. "The Language of Men isn't just a beautifully written memoir about a Vietnam vet father and the complicated legacy he leaves to his son; it's also a distrurbing , brutally honest, darkly funny meditation on masculinity, violence, and sexuality." -- Tom Perrotta, The Leftovers.
Keywords: D'Aries, Anthony, -- 1982-; Family and relationships -- Biography; Interpersonal relationships -- Biography